PERBANDINGAN YIELD TO MATURITY DAN (RATING) PADA SUKUK IJĀRAH DAN SUKUK MUḌĀRABAH - Ilmiah, Dunyati (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
Yield to Maturity is the total return anticipated on a bond if the bond is held until it matures, with purpose of investing current funds and will be received when it maturity with the terms of the profit level of each contract. Risk of sukuk investment, it can be seen from the sukuk rating  that reflects the state of the sukuk issuer company. Yield to maturity and rating are related to investor considerations before deciding on investments, namely return and risk on ijārah sukuk and muḍārabah sukuk. Population of this study rating in 2011-2016 from PT. Pefindo, sample used 42 observation data and analysis using the t-test. The results of this test that there is a significant difference between the yield of ijārah sukuk and muḍārabah sukuk based on yield to maturity and there is no significant difference between the rank of ijārah sukuk and muḍārabah sukuk based on ratings.